Hawker Siddeley aviation and dynamics, 1960-77 - Skinner, Stephen (Crowood aviation series, 2014)
In 1934-35, Gloster, Avro, Armstrong Siddeley, Armstrong Whitworth and others were taken over to create the Hawker Siddeley Group. The Group built some of the most important aircraft and missiles of the 1960s, 1970s and beyond. This title tells their story.